The "white" ethnic racism" thesis: Application to Greek Americans - Petropoulos, Nicholas P. (The Greek Review of Social Research, 1978)
The present report used data collected predomin antly from second-generation Greek-Americans to test the white-ethnic racism thesis. The thesis states that the descendants of «new immigrant» groups — especially their working class descendants, are prejudiced toward minorities, particularly toward blacks. Two approaches were used to evaluate the thesis. In the first approach, a number of ethnic indicators (e.g. demographic, attitudinal, cognitive, and behavioral) were compared to the respondent’s level of tolerance toward Jews and blacks. Some associa tion between «Greekness» and prejudice was noted. There was no uniformity, however, across indicators, with some ethnic indicators (e.g. low assimilation orientation) being correlatedwith intolerance toward the Jews and other ethnic indicators (e.g. number of years in Greek school) being associated with rejec tion of stereotypes about blacks. In addition, there were few strong correlations between the various ethnic indicators and prejudice. Finally, some of the associations between ethnicity and prejudice were not robust when more.traditional correlates of prej udice. such as educational level and authori tarianism, were controlled. Thus, the ethnic factors had a limited predictive capacity. This, however, does not mean that the «universal» correlates of prej udice, such as education and authoritarianism, can not interact with cultural tradition to produce a high level of racism. The white-ethnic racism thesis was also tested under standardized conditions of economic status. Two indices of economic status, reported annual in come and the rental value of the respondent’s dwell ing, were used. Once again there was no uniform support for the thesis. There was more support for the thesis («Greekness» associated with prejudice underlow economic status) when rental value, rather than income, was used as the economic variable. In part this may be due to the better distribution of the rental value than the income factor. It may also be a function of the differential meaning of the two status indicators to the Greek-American respondents. The rental value status is more interwoven with house ownership which is a more tangible and overt indi cator of status than income. In addition, housing has been associated with fears about desegregation. There was more support for the white-ethnic ra cism thesis in the case of stereotypes about blacks than attitudes toward the blacks (social distance) or attitudes toward the Jews. This may be due to thefact that the stereotype measure contained content evok ing the Greek-American’s «bootstrap attitudes». According to this attitude, the descendant of the new immigrant claims that his ancestors were also the vic tims ofnordic prejudice, but diligence, individual ef fort, and patience led to their contemporary success. Thus, they feel they can not be sympathetic with a group who they think is demanding rewards without commensurate efforts. The «bootstrap» mentality assumes a parallelism of experiences between the white ethnics and racial minorities. This parallelism, however, breaks down when other objective factors are taken into account. First, the degree of prejudice against white ethnics cannot match the degree of overt, organized racism against blacks. In part, this is the result of the ethnics being a «cultural» rather than a «racial» minority. In part, it is due to the fact that the blacks have had the stigma of slavery at the hands of the «dominant» WASP group. Finally, the «white ethnics» came to the US at a time (1880-1930) when the country was industrializing and offered much opportunity for en trepreneurial success. When the blacks really began «arriving» in the US (i.e. when their genuine libera tion began in the 1940s and 1950s), the US technol ogy was exceedingly complex and the business oppor tunities were more limited. These factors, however, are rarely considered by the descendants of white ethnics whose relative status is being challenged by the just demands of the racial minorities. The findings ofthe present study — and the atten dant interpretations — can only be suggestive. There is a need to obtain better variation on the ethnicity variables such as generational status and regional origin. Along the same lines, better variation must be sought in the prejudice measures. In the present study, two of these measures (attitudes toward the Jews and social distance attitudes toward the blacks) were not as well distributed as the black stereotype measure. Thus, some of the findings may be due to methodological rather than theoretical reasons. These problems can be rectified if research is carried out in large Greek communities such as Chicago and New York. The white-ethnic racism thesis can, of course, also be tested on other «white-ethnic» groups from Southern and Eastern Europe, both on the micro- and macrosociological levels of analysis.